PELUANG DAN TANTANGAN SUBSEKTOR PERIKANAN DALAM MENOPANG PEREKONOMIAN PROVINSI BANTEN - Reza Septian Pradana (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2019)
This study aims to analyze the opportunities and challenges of fisheries subsector in supporting the economy of Banten Province through studying the growth of fisheries subsector, either capture fisheries or aquaculture and the influented factors. This study uses multiple regression. This study found that the number of outboard motor and inboard motorboat significantly give positive influence to the production of capture fisheries in Banten Province. It can be the opportunity to increase the production of capture fisheries that can support the economy of Banten Province. On the other hand, the indication of overfishing in shallow water showed by the insignificance of nonpowered motorboat number to influent the production of capture fisheries becomes the challenge of capture fisheries in supporting the economy of Banten Province. Then, the lack of fish cultivator skill showed by the negative influence of fish cultivator to the production of aquaculture and the lack of productivity in aquaculture area showed by the insignificance of aquaculture area to influent the production of aquaculture becomes the challenge of fisheries subsector in supporting the economy of Banten Province.